Coming (OUT) the Museum: Cinematographic Engagements through Outfest’s LGBTQI+ Arts and Media Virtual Museum - Santaera, Giovanna (Mimesis Journal, 2024)
The article presents the concept and strategies through which the OutMuseum, an LGBTQI+ arts and media virtual museum, originated from university film organizations and festivals, focuses on the engagement of diverse audiences through a digital platform centered on queer cinema and topics. To grasp the novelties of the model the first section provides an overview of the development of digital museums focused on the cinematographic heritage. The second section examines how exploring various forms of mediation shapes the performative-oriented digital museum model. The final part offers an overview of the digital exhibitions as valuable reference points for future applications.